Perencanaan Lanskap Konservasi Budaya Suku Baduy Luar dan Dangka dengan Pendekatan Bioregion - PRATAMI, DEASNY; PRAMUKANTO, QODARIAN (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017, 2017)
The Baduy Tribe is a community which preserves their own culture, tradition, and believe. The Baduy Tribe has suffered some external influence towards their culture, especially effecting the Outter Baduy and Dangka community which functions as buffer for the Inner Baduy region. The general purpose of this research is to plan a cultural conservation landscape for the Outter Baduy and Dangka Tribe base on bioregion approach. Bioregion constitutes the geographical area, which its delineation is not determine by administrative or political boundaries, instead its limited by the culture domain and the nature boundaries. The research consists of: preparation, preliminary study, analysis, synthesis, and planning. Analysis is done to determine the bioregion units. Evaluation was done by matching the bioregion characteristic of Inner Baduy with bioregion characteristic of Outter Baduy and Dangka. The evaluation result was utilise the to develop a concept to lead in the landscape planning to be developed. The bioregional based of planning concept has a purpose to improve the quality of life by combining nature as a resource and human need, through optimalization the environment sustainable. The final result is arranged as landscape planning for cultural landscape conservation of The Outter Baduy and Dangka Tribe.